Gigantic Reactive Lesion of Mandibular Gingival Tissue (International Journal of Medical and Surgical Sciences, 2017)
Irritation fibroma are the most common form of reactive lesions found within the oral cavity. These lesions normally attain a small size and show a slow growth rate. This paper reports a case of gigantic intraoral irritational fibroma with a history of rapid growth. Complete excision was performed and the specimen was sent for immunohistochemistry (IHC) staining. It was found positive for vimentin, hence reported as irritation fibroma.
Keywords: Oral Irritation Fibroma; Immunohistochemistry; Vimentin